Chemical Compositions in Winter PM2.5 in Changzhou of the Yangtze River Delta Region, China: Characteristics and Atmospheric Responses Along With the Different Pollution Levels - Zhao, Zhuzi; Sun, Ning; Zhou, Wenlin; Ma, Shuaishuai; Li, Xudong; Li, Malong; Zhang, Xian; Tang, Shishi; Ye, Zhaolian (Frontiers in Environmental Science, 2022)
Changzhou, a typical industrial city located in the center of the Yangtze River Delta (YRD) region, has experienced serious air pollution in winter. However, Changzhou still receives less attention compared with other big cities in YRD. In this study, a four-month PM2.5 sampling campaign was conducted in Changzhou, China from November 1st, 2019, to February 1st, 2020. The period covers the entire wintertime and includes first week of the Level 1 response stage of the lockdown period due to the outbreak of COVID-19. The mean PM2.5 concentrations were 67.9 ± 29.0 µg m-3, ranging from 17.4 to 157.4 µg m-3. Secondary inorganic ions were the most abundant species, accounting for 37% and 50% during the low and high PM2.5 pollution periods, respectively. Nitrogen oxidation ratio (NOR) during the high PM concentration level period was twice the low PM concentration period whereas sulfur oxidation ratio (SOR) showed a less significant increase. This represents that nitrate formation is potentially the predominant factor controlling the occurrence of PM pollution. The analysis of NOR, SOR as functions of relative humidity (RH) and ozone (O3) concentrations suggest that the sulfate formation was mainly through aqueous-phase reaction, while nitrate formation was driven by both photochemistry and heterogeneous reaction. And, excess ammonium could promote the formation of nitrate during the high PM period, indicating that ammonia gas played a critical role in regulating nitrate. Furthermore, a special period-Chinese New Year overlapping first week of COVID-19 lockdown period, offered a precious window to study the impact of human activity pattern changes on air pollution variation. During the special period, the average PM2.5 mean concentration was 60.4 μg m-3, which did not show in a low value as expected. The declines in nitrogen oxide (NOx) emissions led to rapid increases in O3 and atmospheric oxidizing capacity, as well as sulfate formation. The chemical profiles and compositions obtained during different periods provide a scientific basis for establishing efficient atmospheric governance policies in the future.